A novel series of cysteine-dependent, allosteric inverse agonists of the nuclear receptor RORγt. Issue 6 (15th March 2020) - Jiang, Xin; Dulubova, Irina; Reisman, Scott A.; Hotema, Martha; Lee, Chun-Yue I.; Liu, Liping; McCauley, Lyndsey; Trevino, Isaac; Ferguson, Deborah A.; Eken, Yigitcan; Wilson, Angela K.; Wigley, W. Christian; et al.
Graphical abstract: Abstract: Inhibition of the nuclear receptor Retinoic Acid Receptor-Related Orphan Receptor γt (RORγt) is a promising strategy for the treatment of autoimmune diseases. In this paper, we describe a series of allosteric, cysteine-dependent, inverse agonists of RORγt. Site-directed mutagenesis and molecular dynamics simulations are supportive of a mechanism of action through specific binding to Cys476 on alpha helix 11 of the ligand binding domain (LBD). Representative compounds in the series selectively inhibit RORγt, potently suppress interleukin-17A (IL-17A) production by human CD4 + T cells, and inhibit T helper 17 (Th17) differentiation from human naïve CD4 + T cells. The advanced compound 13 is orally bioavailable and active at a dose of 3 mg/kg in a murine collagen-induced model of rheumatoid arthritis. Collectively, these data are supportive of the development of compound 13 in autoimmune diseases.